PENGUATAN KARAKTER TANGGUNG JAWAB MELALUI POLA ASUH DEMOKRATIS (STUDI DI PANTI ASUHAN YATIM PUTRI ‘AISYIYAH KARANGANYAR) - Mulyani, Mulyani (PKn Progresif, 2015)
The implementation of the strengthening of character through the responsibilities of democratic parenting is implemented through: 1) Parenting democratic, 2) implementation of obligations, 3) Modeling, and 4) Planting of religion values. In practice there are several barriers experienced that came from the caregivers, and foster children such as: relationships influences from within and outside the orphanage, and the amount of caregivers is less than the amount of foster children. Although the implementation of the responsibility of strengthening character through democratic parenting  is less than the maximum but the responsibility is always shown in the form of foster children in everyday life, such as: 1) responsibility to God, for example by carrying out obligatory prayers, 2) responsibility self as body hygiene and 3) responsibility for the orphanage, for example, always keep the good name of the orphanage.